Analisis Temperatur Dan Entalpi Peleburan Sarang Lebah Di Kabupaten Aceh Besar Provinsi AcehMenggunakan Metode T-History - Ully Muzakir (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2015)
The capacity of energy storage and temperature storage has come into consideration in choosing thermal energy storage system. Absorbed or released material either big or small can be determined by finding the value of the specific heat (Cp) and the latent heat fusion (HL). The selection of materials suitable for Phase Change Materials (PCM) latent heat storage system is the most difficult but the most important thing. The determination of specific heat (Cp), latent heat (H) and thermal conductivity (k) of the PCM is very important in order to assess its performance for the process of developing a good and superior PCM. with a lot of bee-wax materials which is in the district of Aceh Besar province of Aceh, the bee-wax materials of this need to be investigated for long-term goals as a PCM. In this study, T-history method is used to determine of specific heat (Cp), latent heat (H) and thermal conductivity (k) of the bee-wax materials. The results of calculations using the T-History for bee-wax materials obtained Cps at 0,03 KJ/Kg.K ; Cp,l at 3,45 KJ/Kg.K ; Hm at 307,15 KJ/Kg ; k at 0,262 W/mK. Based on these data, the bee-wax in Aceh Besar district can be used as a Phase Change Materials (PCM). Keywords : bee-wax materials, T-history method, specific heat, latent heat, thermal conductivity